2022
DOI: 10.3390/healthcare10091722
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Healthcare Workers’ Knowledge and Their Confidence in the Diagnosis and Management of Human Monkeypox: A Cross-Sectional Study in a Middle Eastern Country

Abstract: The ongoing multi-country human monkeypox (HMPX) outbreak was declared as a public health emergency of international concern. Considering the key role of healthcare workers (HCWs) in mitigating the HMPX outbreak, we aimed to assess their level of knowledge and their confidence in diagnosis and management of the disease, besides the assessment of their attitude towards emerging virus infections from a conspiracy point of view. An online survey was distributed among HCWs in Jordan, a Middle Eastern country, duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
77
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(108 citation statements)
references
References 61 publications
(98 reference statements)
10
77
4
Order By: Relevance
“…On the other hand, Norhayati et al found that the pooled proportion of COVID-19 vaccine acceptance was the highest in Southeast Asia at 74% and the lowest in the Eastern Mediterranean region at 52% [ 93 ], which was consistent with an earlier review, which found that COVID-19 vaccine acceptance was over 90% in Southeast Asia, with the lowest proportions of acceptance in the Middle Eastern countries [ 9 ]. The Middle East’s low vaccine acceptance was linked to the widespread belief in conspiracies regarding emerging virus infections and subsequent control measures that harmed vaccination acceptance and uptake [ 87 , 111 , 112 ]. Furthermore, these variations may reflect varying levels of trust in information from government sources.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Norhayati et al found that the pooled proportion of COVID-19 vaccine acceptance was the highest in Southeast Asia at 74% and the lowest in the Eastern Mediterranean region at 52% [ 93 ], which was consistent with an earlier review, which found that COVID-19 vaccine acceptance was over 90% in Southeast Asia, with the lowest proportions of acceptance in the Middle Eastern countries [ 9 ]. The Middle East’s low vaccine acceptance was linked to the widespread belief in conspiracies regarding emerging virus infections and subsequent control measures that harmed vaccination acceptance and uptake [ 87 , 111 , 112 ]. Furthermore, these variations may reflect varying levels of trust in information from government sources.…”
Section: Discussionmentioning
confidence: 99%
“…Previous and current evidence show unsatisfactory monkeypox knowledge among healthcare workers and students in health schools [ 123 , 124 , 125 , 126 ]. In addition, low levels of confidence to diagnose and manage monkeypox were shown in various settings [ 127 , 128 ]. This highlights the urgent need for educational and training intervention measures to help in the prevention and proper control of the ongoing outbreak.…”
Section: Preventionmentioning
confidence: 99%
“…In a recent review by Di Gennaro et al, the implementation of proper public health responses to contain the MPXV spread was delineated comprehensively [ 70 ]. Specifically, the specific actions at both the community and healthcare settings included: (1) vigilant surveillance for early detection and isolation of cases [ 70 ]; (2) training of healthcare workers to enable accurate and timely clinical diagnosis considering the current evidence of low self-reported confidence in the ability to diagnose and manage the disease among physicians and nurses [ 123 , 127 , 128 ]; (3) availability of accurate laboratory diagnostic kits cannot be overlooked, in light of the long list of differential diagnoses for patients presenting with unexplained acute rash with other nonspecific symptoms [ 70 , 71 ]; and (4) adherence to proper infection control measures, including the use of PPE and disinfection procedures [ 70 ].…”
Section: Preventionmentioning
confidence: 99%
“…Other authors have reported a higher rate, with 69.8% of physicians that knew about a speci c monkeypox vaccine according to a study from Saudi Arabia [22]. On the other hand, lower percentages have been reported in Jordan (33.3%), and Indonesia (36%) [21,31]. It is worth mentioning that by the time our study was conducted, only a few countries had started their vaccination campaign, and none of the Latin American countries had monkeypox vaccines available [32,33], all of which could have explained why almost 40% of our study population was not familiar with the vaccine.…”
Section: Discussionmentioning
confidence: 96%